Regional variations in incidence of surgical site infection and associated risk factors in women undergoing cesarean section: A systematic review and Meta-Analysis - Nazmul, Islam (2025)
BackgroundSurgical site infections (SSIs) are the most common postoperative complications after cesarean section (CS), with increased mortality, prolonged hospital stays, and increased healthcare costs. ObjectiveTo systematically estimate the global incidence and identify the risk factors associated with SSI, focusing on the variation between high- and low-income countries. Search strategy and selection criteriaObservational studies reporting on the incidence of SSI after CS were systematically searched in PubMed, Embase and SCOPUS. Data collection and analysisMultiple authors independently screened, extracted the data, and assessed therisk of bias. The primary outcome was the incidence of SSI within 30 days. Subgroup and sensitivity analyses and meta-regression examined SSI-related heterogeneity. Main results49 cohort studies with 271,954 participants met the inclusion criteria. We found with moderate certainty that the overall SSI incidence in CS patients was 7.0 % (95 % CI: 6.0 %–8.0 %). The SSI incidence in LMICs was 8.0 % (95 % CI: 6.0 %–10.0 %) with moderate certainty, while the incidence in HICs was 5.0 % (95 % CI: 4.0 %–7.0 %) with low certainty. Subgroup analysis indicated a significantly higher incidence in Africa and the Western Pacific. Meta-regression showed a significant decrease in SSI incidence in HICs. Maternal factors, procedural aspects, and care quality were associated with SSI. ConclusionsOur findings offer valuable insights into the global incidence of SSIs following CS and provide a reliable estimate for benchmarking and quality improvement. This study adds to the evidence on SSI determinants and highlights the need for targeted preventative measures across various regional and healthcare settings. Implications for clinical practiceHigher SSI rates in LMICs call for targeted infection prevention strategies, including improved preoperative preparation, antibiotic prophylaxis, and enhanced antenatal care services. In HICs, addressing lifestyle factors, managing comorbidities, and refining surgical protocols can further mitigate risks, emphasizing the need for region-specific, evidence-based interventions.